Penambahan Berbagai Berat Busa Filter Rokok Sebagai Adsorben Terhadap Penurunan Emisi Gas Buang Karbon Monoksida (CO) Pada Knalpot Sepeda Motor - Gede Nugraha; Sigid Sudaryanto; Tuntas Bagyono (Sanitasi: Jurnal Kesehatan Lingkungan, 2011)
Air pollution in Indonesia is estimated 70% comes from exhauster emission of motor vehicles, of which gasoline contributes for 70% carbon monoxide (CO). One of efforts for controlling exhauster emission is by modifying the exhauster system itself. In this study the modification is conducted by adding cigarette filter as gas adsorbent. The objectives of the study was to determine the effect of adding various weight cigarette filters in decreasing the carbon monoxide emission, and to know the most effective weight by conducting an experiment which followed one group pre-test post-test design. The gas sampling was measured 15 times on each of the cigarette filter weight. The results showed that the 40, 50 and 60 grams cigarette used reduced the CO concentration, and the most effective weight was the 40 grams which could decrease the CO in 2.00% average with overall percentage decrease of 48.14%.